Pengaruh Gaya Kepemimpinan Dan Sistem Pengendalian Internal Terhadap Pencegahan Fraud Pengelolaan Dana Desa (Studi Kasus di Desa Tana Duen, Kecamatan Kangae, Kabupaten Sikka) - Maria Evanggelisa Dua Pagang; Yosefina Andia Dekrita; Wihelmina M.Y Jaeng (Universitas Nusa Nipa Maumere, 2025)
This study aimed to determine the influence of leadership style and the internal control system on the prevention of fraud in village fund management in Tana Duen Village, Kangae District, Sikka Regency. The research employed a quantitative analysis technique with data obtained from primary sources through the distribution of questionnaires. The population consisted of all village officials and community members in Tana Duen Village, Kangae District, Sikka Regency. The sampling technique used was saturated sampling, with a total sample of 40 respondents. Data were analyzed using multiple linear regression with IBM SPSS Statistics 26. The Result showed that leadership style had a significant effect on the prevention of fraud in village fund management. The internal control system also had a significant effect on fraud prevention efforts. Furthermore, the combination of leadership style and internal control system significantly influenced the prevention of fraud in village fund management.